Profil Keterampilan Berpikir Kritis Peserta Didik SMA pada Materi Energi Terbarukan - Yanti Yuliarti; Leni Marlina; Sardianto Markos Siahaan; Apit Fathurohman; Sudirman Sudirman (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the critical thinking profile of high school students on renewable energy materials using a mixed method consisting of qualitative descriptive in the form of interview results and quantitative descriptive in the form of test result analysis at SMA Negeri 1 Sembawa, South Sumatra Province. The interview results stated that students are not used to doing critical thinking problems and rarely do activities that can stimulate their critical thinking skills. The test for the learners showed a low average score of 35.12. The average score obtained for the indicator giving a simple explanation was 33.80, the indicator building basic skills was 38.19, and the indicator giving further explanation was 21.53. All three include critical thinking skills categorized as lacking. As for the indicators inferring and organizing strategies (tactics) included in the category enough with average scores of 43.75 and 40.97. The results indicate that students' critical thinking skills fall into the category of being less proficient. This is due to students' lack of literacy regarding renewable energy and their unfamiliarity with working on questions with high-level thinking skills. Another cause is that physics learning is less varied and experiments are rarely carried out.